2002
DOI: 10.1159/000063658
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline Treatment Increases Retinal Dopamine Content in Rabbits

Abstract: Citicoline (exogenous cytidine-5′-diphosphocholine) was reported to enhance dopaminergic neurotransmission in the brain. A few clinical studies showed beneficial effects of this drug on the function of the visual pathway in patients with glaucoma or amblyopia. The present study was aimed at determining whether citicoline could influence retinal catecholamine levels in adult male Albino rabbits. The animals received the drug (50 mg/kg i.p., twice daily) or vehicle for 7 days, and retinal catecholamine concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 17 publications
3
44
1
1
Order By: Relevance
“…Therefore, stimulation of the dopaminergic system caused by CDP-choline may be a common mechanism that causes both an improvement in the motor symptoms experienced by patients suffering from Parkinson's disease and an improvement in the retinal and post-retinal performance of glaucomatous patients. In accordance with this theory, it was observed that in rabbits treated with CDP-choline [33] the concentration of dopamine in the retina increased.…”
Section: Introductionsupporting
confidence: 63%
“…Therefore, stimulation of the dopaminergic system caused by CDP-choline may be a common mechanism that causes both an improvement in the motor symptoms experienced by patients suffering from Parkinson's disease and an improvement in the retinal and post-retinal performance of glaucomatous patients. In accordance with this theory, it was observed that in rabbits treated with CDP-choline [33] the concentration of dopamine in the retina increased.…”
Section: Introductionsupporting
confidence: 63%
“…Conversely, dopaminergic uptake has been associated with improved performance on working memory and executive function tasks requiring attention [25,26]. Previous investigations have shown that citicoline increases dopamine [10,27], increases dopamine receptor densities [28], and aids in protection of neurons related to dopamine [29]. While dopamine was not measured in the current study, it seems likely that dopamine increases identified with citicoline supplementation may explain the improved performance on attention tasks shown in the present study.…”
Section: Discussioncontrasting
confidence: 46%
“…A second mechanism that may explain why citicoline improves function in chronically injured animals focuses on observed decreases in dopamine following injury (Yan et al, 2001). In such models, citicoline increased dopamine levels (Ross et al, 2001;Rejdak et al, 2002;Secades and Frontera, 1995), which enhances neurorecovery (Kline et al, 2004).…”
Section: Methodsmentioning
confidence: 99%